Managing Thrips and Tospoviruses in Tomato - Joe Funderburk; Josh Freeman; Scott Adkins; Sam Hutton; Philip Stansly; Hugh Smith; Gene McAvoy; Crystal Snodgrass; Mathews Paret; Norm Leppla (EDIS)
Several invasive species of thrips have established in Florida and are causing serious economic losses to vegetable, ornamental, and agronomic crops. Damage to crops results from thrips feeding and egg-laying injury, by the thrips vectoring of plant diseases, the cost of using control tactics, and the loss of pesticides due to resistance. This updated fact sheet describes the biology and ecology of thrips and tomato spotted wilt virus, and recommends a management program.